FX swaps, shadow banks and the global dollar footprint. (June 2023) - Dafermos, Yannis; Gabor, Daniela; Michell, Jo
The era of dollar-based financial globalisation has seen a steady rise in the use of foreign exchange (FX) swaps. We provide a macrofinancial political economy perspective on the geography of FX swaps, and the spatial effects of central bank policies aimed at taming instabilities associated with the uneven geography of the dollar. First, we analyse the mechanisms and potential sources of instability involved in accessing dollars using FX swaps and repurchase agreement (repo) contracts, respectively, in both private and public (central bank) use. Second, we show that the distribution of currencies and institutions involved in trading swaps is skewed, reflecting both the dominance of the dollar as international financing currency and the uneven international distribution of dollar-denominated assets and liabilities. We document the changing composition of dollar swap users on both the long-dollar and short-dollar side and identify potential sources of macrofinancial vulnerability for dollar lenders and borrowers. The Fed's approach to global liquidity provision via both swaps and repos constitutes a spatially variegated strategy to preserve the hegemony of the US dollar. Despite its partial success in reducing instability due to cross-border financial imbalances, the Fed's uneven and hierarchical lender of last resort approach cannot sufficiently stabilise global finance to underpin a new era of macrofinancial stability.